A Literary Interpretation of Blood Symbolism in Ifá Divination Poetry - Oluwabunmi Tope Bernard (Yoruba Studies Review, 2021)
Tis study undertakes a literary analysis of blood as a symbol as contained in the Ifá divination poetry among the Yorùbá of Southwestern Nigeria, which the researcher has collected through personal observations, consultations, and interviews with Ifá priests. Using Ricoeur’s hermeneutics theory of interpretation, the findings show that the selected Ifá divination poems present the symbolic interpretations of blood in Ifá corpus as it is entrenched in the Yorùbá psychology, sexuality, religiosity, worldview, identity and kinship. The paper presents that blood is multifaceted among the Yorùbá.